Dimensi Teologis Tantra Di Nusantara: Sebuah Kajian Literatur - Ida Made Windya (Widya Sandhi, 2026)
This study explores the theological dimensions of Tantra in the Nusantara through a systematic literature review. Applying the PEOS framework and PRISMA guidelines, articles were screened from Google Scholar and GARUDA using the keywords “Tantra,” “Tantrayāna,” “Nusantara,” “ritual,” and “theology,” restricted to publications between January 1, 2020, and August 15, 2025. Four articles met the criteria for analysis. Results indicate that Tantric theology is reflected in the Śiva-Śakti principle, the body as microcosm, cosmic energy, and ritual instruments such as mantra, mudrā, and yantra. Integration occurred via symbolic assimilation, iconography, and daily practice. The study demonstrates that Tantra is not only an esoteric tradition but also a theological foundation shaping Hindu-Buddhist spirituality in the Nusantara.